7(2n+3n)=2(6n+9)

Simple and best practice solution for 7(2n+3n)=2(6n+9) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(2n+3n)=2(6n+9) equation:



7(2n+3n)=2(6n+9)
We move all terms to the left:
7(2n+3n)-(2(6n+9))=0
We add all the numbers together, and all the variables
7(+5n)-(2(6n+9))=0
We multiply parentheses
35n-(2(6n+9))=0
We calculate terms in parentheses: -(2(6n+9)), so:
2(6n+9)
We multiply parentheses
12n+18
Back to the equation:
-(12n+18)
We get rid of parentheses
35n-12n-18=0
We add all the numbers together, and all the variables
23n-18=0
We move all terms containing n to the left, all other terms to the right
23n=18
n=18/23
n=18/23

See similar equations:

| -2a=-15-6a | | -1x+9=14 | | x-(-7)=63 | | x2+3=6 | | 3-5v=-8 | | 6x-7=60 | | -6=10+4x | | 3/5m=-3 | | 3(.5y+4)+y=7 | | 863=y-716 | | 3-(5a-3)=8a+12 | | 3(1-0a+22a=2(2a-9)-15 | | 48x+2=23x+4 | | -8-8p=-4+12 | | 3-5a-3)=8a+12 | | (x+6)(x-6)=108 | | 2x+2-6=3x+5 | | 1/2(e-3)-2=2e+1 | | 5(r+9)-2(1-r)=11 | | 4(5n+7)=10+2n | | -24+40w=20 | | (4x+4)+(6x-7)=90 | | -18=r/17 | | 3/4x+1/4=7/4 | | 40=2x+5x-1 | | 2x+4=1(x+3) | | 1/4(8x-12)x=6 | | 10=m/27 | | 40=2x= | | 4x+27=6x-23 | | 1/3h-2=1 | | 19=k/20 |

Equations solver categories